Investigation of microwave sensor and integrate with polydimethylsiloxane for medical imaging application - Nurhasniza Edward; Lavanya Paramasivam; Zahriladha Zakaria; Amyrul Azuan Mohd Bahar (Institute of Advanced Engineering and Science, 2021)
The small-sized wideband antenna is one of the antennas used in the medical field to detect body tissue. The antenna's direct contact with the human body causes reflected signal due to the high body coupling, and the narrower bandwidth tends to reduce the data transfer rate in transmission. Therefore, this paper aims to design a wideband antenna with wearable properties operated in the frequency range of 3 GHz to 6 GHz. The antenna is designed with a rectangular-shaped patch with notches and the t-slot shaped partial slot ground. The connected speech test (CST) studio suite software is used to design and optimize the miniature antenna, which measures 24 mm (W) x 38 mm (L) x 0.168 mm (H). The antenna is then embedded with polydimethylsilixane (PDMS) at the top half of the antenna with the dimension 24 mm (W) x 19 mm (L) x 1 mm (H) and also fully occupied. The antenna is configured with the bending capabilities to adapt the human body surface at an angle of 30º. The antenna is having the benefits of small size, cost-effective, and easy to fabricate. The antenna design can effectively detect unusual body tissue, and it safe to be used.